Identification and Characterization of Novel Small RNAs in Rickettsia prowazekii - Schroeder, Casey L. C.; Narra, Hema P.; Sahni, Abha; Rojas, Mark; Khanipov, Kamil; Patel, Jignesh; Shah, Riya; Fofanov, Yuriy; Sahni, Sanjeev K. (Frontiers in Microbiology, 2016)
Emerging evidence implicates a critically important role for bacterial small RNAs (sRNAs) as post-transcriptional regulators of physiology, metabolism, stress/adaptive responses, and virulence, but the roles of sRNAs in pathogenic Rickettsia species remain poorly understood. Here, we report on the identification of both novel and well-known bacterial sRNAs in Rickettsia prowazekii, known to cause epidemic typhus in humans. RNA sequencing of human microvascular endothelial cells (HMECs), the preferred targets during human rickettsioses, infected with R. prowazekii revealed the presence of 35 trans-acting and 23 cis-acting sRNAs, respectively. Of these, expression of two trans-acting (Rp_sR17 and Rp_sR60) and one cis-acting (Rp_sR47) novel sRNAs and four well-characterized bacterial sRNAs (RNaseP_bact_a, α-tmRNA, 4.5S RNA, 6S RNA) was further confirmed by Northern blot or RT-PCR analyses. The transcriptional start sites of five novel rickettsial sRNAs and 6S RNA were next determined using 5’ RLM-RACE yielding evidence for their independent biogenesis in R. prowazekii. Finally, computational approaches were employed to determine the secondary structures and potential mRNA targets of novel sRNAs. Together, these results establish the presence and expression of sRNAs in R. prowazekii during host cell infection and suggest potential functional roles for these important post-transcriptional regulators in rickettsial biology and pathogenesis.